2014
DOI: 10.1210/jc.2014-2094
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of AIP Gene Mutations in Young Patients With Acromegaly: A Registry-Based Study

Abstract: The frequency of AIPmut in this registry-based cohort of young patients with acromegaly is lower than previously reported. Patients with a positive family history should be tested for an AIPmut, whereas young patients without an apparent family history should be screened, depending on the individual cost to benefit ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 19 publications
3
13
0
1
Order By: Relevance
“…AIP mutations were detected in 2-4% of young acromegalic patients with sporadic microadenoma and macroadenoma [17]. In our sporadic somatotropinomas AIP was positive in over 80% of tumours, which is in line with other studies [27], while Kasuki et al found low expression in only about 50% of somatotropinomas [18].…”
Section: Prace Oryginalnesupporting
confidence: 91%
See 1 more Smart Citation
“…AIP mutations were detected in 2-4% of young acromegalic patients with sporadic microadenoma and macroadenoma [17]. In our sporadic somatotropinomas AIP was positive in over 80% of tumours, which is in line with other studies [27], while Kasuki et al found low expression in only about 50% of somatotropinomas [18].…”
Section: Prace Oryginalnesupporting
confidence: 91%
“…Germline mutations of AIP are associated with familial isolated pituitary adenoma (FIPA) secreting hGH and/or PRL, found in young patients [16]. There are no somatic AIP mutations [17]. Mutant AIP loses the ability to reduce cell proliferation.…”
Section: Prace Oryginalnementioning
confidence: 99%
“…In sporadic acromegaly, overall AIP mutation prevalence was reported as 3.1-16 % [10][11][12]26]. In selected acromegalic populations such as patients diagnosed with a macroadenoma before the age of 30, the ratio is reported as 2.3 or 13.3 % in different studies [18,27] or patients diagnosed before the age 40 as 4 % [28] or patients with resistance to SSA as 4 % [24]. These studies were carried out in patients from different regions of Europe.…”
Section: Discussionmentioning
confidence: 99%
“…AIP gene defects are less common in sporadic pituitary adenomas identified in up to 8% of all cases [10,11]. However, when younger patients (<30 years old) with macroadenomas, or children and adolescents <18 years old are selected, up to 20.5% of cases with sporadic PAs may harbor an AIP mutation [12][13][14][15]. The exact mechanism of the pituitary tumorigenesis with AIP mutations is not clear.…”
Section: Familial Isolated Pituitary Adenomas (Fipa)mentioning
confidence: 99%